EMPOWERMENT OF PKK COOPERATIVE JULI COT MEURAK TO INCREASE COMMUNITY INCOME IN ORDER TO SUPPORT SDGS AND ACCELERATE THE ERADICATION OF EXTREME POVERTY (P2KE) - Mai Simahatie; Cut Fadhilah; Imam Malik; Ashraf Mauliddin; Nuratul Syiva; Rizaki Akbar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
One of the strategies used to empower women is to empower "women's cooperatives" as a means of additional capital in opening micro, small and medium enterprises (MSMEs) for women. Cooperatives have a fairly large role in economic life, because cooperatives are legal entities based on family as stated in Article 33 of the 1945 Constitution. In Bireuen, there is a cooperative owned by the PKK mothers of Juli Cot Meurak Timur Village, Bireuen Regency. This cooperative is used to provide business capital loans to housewives who want to increase their business capital or open a business such as selling fried foods, selling cakes, handicrafts, and so on. Sharia cooperatives are one type of cooperative that operates based on Islamic sharia principles. The goal is to support the economic welfare of its members through savings and loan activities and business financing that is halal, free from usury, gharar (uncertainty), and maisir (speculation). This cooperative usually has several main characteristics, namely, Sharia Financing Using sharia contracts such as mudharabah (cooperation between capital owners and managers), murabahah (buying and selling with agreed profits), and musyarakah (profit sharing cooperation). Profit Sharing System Sharia cooperatives share profits based on a previously agreed ratio between members and the cooperative, not through interest. Supervision of the Sharia Board This cooperative is generally supervised by the Sharia Supervisory Board. The Board of Directors (DPS) to ensure that business activities remain in accordance with sharia principles, Focus on Islamic Values ​​Islamic cooperatives promote business ethics and values ​​such as justice, transparency, and social welfare for all members and Halal Products and Services Products or investments made must meet halal criteria, both from their source and their use